1987
DOI: 10.1182/blood.v69.6.1712.1712
|View full text |Cite
|
Sign up to set email alerts
|

A novel platelet aggregating factor found in a patient with defective collagen-induced platelet aggregation and autoimmune thrombocytopenia

Abstract: We found a novel platelet aggregating factor in a patient with steroid- responsive immune thrombocytopenic purpura that is associated with defective collagen-induced platelet functions. The aggregating factor and platelet functions were analyzed. The patient, a 58-year-old female, had purpura and prolonged bleeding time despite adequate platelet counts (greater than 140,000/microL) after steroid therapy. The patient's platelets responded normally to all agonists except collagen. Platelet adhesion to collagen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The distinct short-term cellular stress and injury induced by the combined thermo-chemotherapeutic tumor treatment was visible by the enrichment of protein pathways belonging to GP6 signaling pathway and coagulation system, which is in agreement with the high impact of this therapy modality on the tumor volume. GP6 is the major signaling receptor for the extracellular matrix protein, collagen [19], and it plays a critical role in hemostasis and thrombosis through integrin activation, supporting adhesion and the initial stages of platelet aggregation [20][21][22]. In agreement with this, collagen fibers, which are being destroyed by magnetically induced heating, are the most thrombogenic macromolecular components of the extracellular matrix [23].…”
Section: Discussionmentioning
confidence: 86%
“…The distinct short-term cellular stress and injury induced by the combined thermo-chemotherapeutic tumor treatment was visible by the enrichment of protein pathways belonging to GP6 signaling pathway and coagulation system, which is in agreement with the high impact of this therapy modality on the tumor volume. GP6 is the major signaling receptor for the extracellular matrix protein, collagen [19], and it plays a critical role in hemostasis and thrombosis through integrin activation, supporting adhesion and the initial stages of platelet aggregation [20][21][22]. In agreement with this, collagen fibers, which are being destroyed by magnetically induced heating, are the most thrombogenic macromolecular components of the extracellular matrix [23].…”
Section: Discussionmentioning
confidence: 86%
“…GPVI is one of the most essential platelet collagen receptors involved in atherothrombosis, and soluble GPVI is rapidly proteolytically cleaved by TxA 2 -induced MMP [38,53]. Since GPVI expression is restricted to platelets and megakaryocytes, it is another potential antithrombotic target [54,55], and in line, patients with a GPVI deficiency do not exhibit symptoms other than a mild bleeding tendency [56][57][58][59][60][61][62][63]. In the present study, the reduction of soluble GPVI plasma levels was not found in low-dose ASA-treated mice compared to control mice.…”
Section: Discussionmentioning
confidence: 99%
“…The first piece of epidemiological evidence validating GPVI as an antiplatelet target was reported in 1987 via the identification of a GPVI deficient patient . Since then numerous cases of acquired (anti-GPVI autoantibodies) and congenital GPVI deficiency (GPVI is not expressed or is not functioning as normal) have been reported and were summarized by Arthur et al in 2007 (Table ).…”
Section: Gpvi: a Promising Antiplatelet Targetmentioning
confidence: 99%